Evaluation of Owners’ Characteristics and Succession Practice among Small and Medium Size Manufacturing Enterprises in Ekiti State, Nigeria - Fayomi, Ezekiel Jide; Fields, Ziska; Arogundade, Kayode Kingsley; Awotunde, Olusegun Matthew; Ijamusan, Olubunmi, Christianah; Onileowo, Temitope Teniola (Journal of Economics and Behavioral Studies, 2019)
This study evaluated owners’ characteristics and succession practice among manufacturing Small and Medium Enterprises (SMEs) in Ekiti State, Nigeria. It assessed the correlation between achieved characteristics (educational level and experience) of owners of manufacturing enterprises and choice of succession practice; and the extent to which owners’ situational characteristics (health, spouse, children’s readiness) influenced the choice of succession practice. The study employed descriptive design and the population comprised of 136 founders and succeeding owners of registered manufacturing SMEs in Ekiti State. To obtain a sample of 100 participants, stratified sampling techniques were used and Descriptive statistics were also used to profile the respondent’s demography. Pearson Product Moment Correlation (PPMC) was employed to determine the association between the demographic and achieved characteristics of owners and succession practice. While multiple regressions were used to analyze learnable and situational characteristics and succession practice the study’s findings revealed that owners’ characteristics, expressed as: demographic characteristics, being female (r=0.315, p=0.012); achieved characteristics, higher education (r=0.300. p=0.017) and average experience (r=0.272, p=0.031); learnable characteristics, need for achievement (β=0.334, p=0.007) and leadership (β=0.288,p=0.035); and situational characteristics of wife (β=-0.256,p=0.04) and children (β=0.284, p=0.018), were significant variables that influenced succession practice among SMEs’ owners. It concluded that practice and belief in succession practices among SMEs owners is strongly influenced by education, experience, and the desire to leave a legacy. Recommendations include that government should encourage graduates to establish SMEs and managers should strive for organized and dependable families and train their children, to ensure successful succession.